Resonant column and cyclic torsional shear tests on Sutlej river sand subjected to the seismicity of Himalayan and Shivalik hill ranges: A case study. Issue 166 (March 2023) - Rohilla, Sakshi; Sebastian, Resmi
Abstract: The study of site-specific dynamic properties of soil holds vital importance in many geotechnical engineering problems for the region holding high active seismicity. The Sutlej River basin, a valley and high-risk seismic zone in the north-eastern part of the Punjab state, has been considered for the study. The site-specific shear modulus reduction curves and material damping ratio curves for a range of shear strain amplitudes have been developed under varying experimental conditions of confining pressure, relative density, and loading frequency using the resonant column (RC) tests and cyclic torsional shear (CTS) tests. The study addresses the usage of two testing approaches, i.e., resonant column test (RC) and cyclic torsional shear test (CTS), for the estimation of shear modulus and damping ratio values at varying shear strain amplitudes. The regression analysis has been performed for the two testing techniques viz. RC and CTS to study the sensitivity of shear modulus values and material damping ratio values towards varying experimental conditions. The shear modulus and damping ratio values determined from cyclic torsional shear tests were observed to have great dependency on the frequency of loading. The knowledge of site-specific dynamic properties will support practical interpretation for the geotechnical engineering problems in the region. Highlights: The resonant column and cyclic torsional shear testing of Sutlej river sand have been performed under varying experimental conditions to analyze the dynamic properties. Site-specific shear modulus reduction and damping ratio curves have been developed under varying relative density, confining pressure, and loading frequency conditions. The influence of frequency of cyclic torsional shear loading on shear modulus and damping ratio has been analyzed. The modified hyperbolic model has been used to assess the non-linear dynamic behaviour of sand.